Pengembangan Kecakapan Hidup Anak Usia Dini Melalui Kuliner Tancok Ayu (Ketan Pencok Bumiayu) sebagai Produk Unggulan Kuliner di KB Mutiara Bunda - Mujayanah, Mujayanah (CV. Supernova Office Stationary and Printing, 2023)
Entrepreneurial spirit is a character that needs to be instilled from an early age. Education entrepreneurship is not just about educating prospective entrepreneurs or teaching children making money early on, but to grow and develop character and build it as a provision of life skills. As one implementation new paradigm of education, term life skills is a skill possessed by a person to want and dare to face the problem live and live naturally without feeling pressured, then proactively and creatively seek and find solutions so finally got over it. This change effort boils down to one goal, namely the attainment of improvement quality of educational outcomes ultimately can improve the quality and standard of living society and nation. This entrepreneurial spirit can be trained through various activities such as culinary processing typical of the city of Bumiayu as superior products through various activities such as cooking classes, outing classes, market days by involving the active role of parents in these activities.